Communication—Pt-Doped Thin Membranes for Gas Crossover Suppression in Polymer Electrolyte Water Electrolysis. Issue 13 (8th August 2019) - Garbe, Steffen; Babic, Ugljesa; Nilsson, Elisabeth; Schmidt, Thomas J.; Gubler, Lorenz
Abstract : Hydrogen gas crossover is a major safety issue in polymer electrolyte water electrolyzers (PEWE) and a limiting factor for the use of thinner polymer electrolyte membranes for high voltage efficiency PEWE. This article outlines a simple impregnation method for a recombination catalyst, yielding high crossover suppression for thinner membranes at differential pressures without negative effects on the cell performance.